The Royal Academy of Engineering, UK and The Enriching of Engineering Education Training and Practice Programme in Sub-Saharan Africa - Nyichomba, Bavo B. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper elucidates initiatives taken by the Royal Academy of Engineering, UK, to overcome barriers in education and training in <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Sub-Sahara African higher learning engineering institutions. The said barriers include mismatches of curriculum, ineffectual teaching and learning and little exposure of academic staff to engineering practice. In order to overcome such barriers, the Royal Academy of Engineering established the two programmes in the region. The first one, Enriching Engineering Education Programme (EEEP) from 2014/15 to 2015/16 where the University of Dar es Salaam coordinated this programme as a hub for East African universities namely; Makerere University (Uganda), Moi University (Kenya), Dedaan Kimathi (Kenya) and Kenyatta Technical University (Kenya). A second programme which was implemented from 2015/16 to 2023/24, the University of Dar es Salaam also acted as a Hub for the local higher learning institutions namely; the Dar es Salaam Institute of Technology, Nelson Mandela, Mbeya University of Science and Technology, Sokoine University of Agriculture and National Institute of Transport under the new Higher Education Partnerships programme in Sub-Saharan Africa (HEPSSA); leaving Moi University and Makerere also to coordinate their own local universities under HEPSSA programme. All the above programmes involved capacity building in enhancing the outcome based curriculum, problem-based learning, academia and industry staff exchange, student placements in industries, and technology business incubators/hubs practices. Conversely, the paper emphasizes the need establishing concordats of universities that will enhance collaboration of universities with industries in establishing joint research and development programmes for practical applications to technical and business problems facing the industry/private sector and the nation as a whole